Pengaruh Kepemilikan Institusional dan Financial Distress terhadap Konservatisme Akuntansi: Studi Empiris pada Perusahaan Manufkatur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Mardian, Elza; Taqwa, Salma (Jurnal Eksplorasi Akuntansi, 2024)
There is one principle in presenting financial reports, namely accounting conservatism. Accounting conservatism is a form of caution in responding to losses or profits in financial reports. In this research, there are factors that can influence accounting conservatism, including institutional ownership and financial distress. The objects of this research are manufacturing sector companies listed on Indonesia Stock Exchange (IDX) in 2018-2022. Samples were obtained based on the purposive sampling method. The research sample obtained was 208 during the 5 year research period. The data analysis used in this research is multiple linear regression using SPSS version 25. The results of this research are that institutional ownership and financial distress have a significant negative influence on accounting conservatism. This research contributes to increasing science and knowledge in the field of accounting as well as factors that influence accounting conservatism in manufacturing sector companies.